Self-paced cycling performance and recovery under a hot and highly humid environment after cooling - Gonzales, B. R.; Hagin, V.; Guillot, R.; Placet, V.; Monnier-Benoit, P.; Groslambert, A. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: This study investigated the effects of pre- and post-cooling on self-paced time-trial cycling performance and recovery of cyclists exercising under a hot and highly humid environment (29.92 °C-78.52% RH).